Antimicrobial and cytotoxic properties of some Malaysian traditional vegetables (ulam) - Mohamed Mackeen, Muhammad Mukram; Ali, Abdul Manaf; El-Sharkawy, Saleh Hassan; Abd Manap, Mohd Yazid; Mohd Salleh, Khalijah; Lajis, Nordin; Kawazu, Kazuyoshi (Swets & Zeitlinger, 1997)
Ethanol extracts of 19 Malaysian traditional vegetables (locally known as ‘ulam’) belonging to 15 families were screened for antimicrobial and cytotoxic activities. Both the disc diffusion (qualitative) and tube dilution (quantitative) assays were employed for the determination of antimicrobial activity against six pathogenic microorganisms, i.e. two Gram-positive bacteria (Bacillus cereus and Bacillus megaterium), two Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa) and two fungi (Aspergillus ochraceous and Cryptococcus neoformans). Six extracts, i.e. Anacardium occidentale, Garcinia atroviridis, Averrhoa bilimbi, Polygonum minus, Diplazium esculentum and Etlingera elatior, showed antimicrobial with minimum inhibitory concentration (MIC) and minimum lethal concentration (MLC) values in the respective ranges of 100 ? 800 µg/ml and 400 ? 800 µg/ml. Seven extracts, i.e. Anacardium occidentale, Garcinia atroviridis, Sesbania grandiflora, Barringtonia racemosa, Polygonum minus, Kaempferia galanga and Etlingera elatior displayed cytotoxic activity against the HeLa (human cervical carcinoma) cell line with CD 50 values in the range of 10–30 µg/ml. The ‘ulam’ show potential as ‘functional food’ in view of the significant therapeutic and nutritive benefits.